2011
DOI: 10.1186/1743-422x-8-184
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic distribution and predominant genotype of the avian infectious bronchitis virus in China during 2008-2009

Abstract: BackgroundThe nephropathogenic avian infectious bronchitis (IB) caused unprecedented economic losses to the commercial chicken industry of China in 2008-2009. To investigate the prevalence of nephropathogenic IB in China, eighty IBV isolates from different provinces during 2008-2009 were identified by dwarf embryo test and RT-PCR.ResultsThe strains were mostly isolated in winter and spring with a wide age range of IB outbreaks, from 4 to 69 days. By the virus recovery trials, 70/80 of the strains resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 39 publications
2
47
1
1
Order By: Relevance
“…The closest relative genotype was IBV LX4, the most predominant variant in China , which shared approximately 87% nucleotide and amino acid identities with isolate ck/CH/LGX/ 111119. There are several publications of the IBV genotype that included ck/CH/LGX/111119, but unfortunately these reports do not agree on genotype designations, such as A2 by Ji et al (2011) and CH III by Luo et al (2012) and Feng et al (2014). Also, the virus genotype designations were inconsistent even in reports by the same research group (Ji et al, 2011;Feng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The closest relative genotype was IBV LX4, the most predominant variant in China , which shared approximately 87% nucleotide and amino acid identities with isolate ck/CH/LGX/ 111119. There are several publications of the IBV genotype that included ck/CH/LGX/111119, but unfortunately these reports do not agree on genotype designations, such as A2 by Ji et al (2011) and CH III by Luo et al (2012) and Feng et al (2014). Also, the virus genotype designations were inconsistent even in reports by the same research group (Ji et al, 2011;Feng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, different strains of IBV have been circulating in the Middle East. For example, IBV variants like Q1 (CK/CH/LDL97I/97) (1,11,14,17,20,26,27), IBV variant-1 (793/B, IS/222/96, IS/251/ 96, and IS/64714/96), IBV variant-2 (IS/223/96, IS/572/98, IS/ 585/98, and IS/589/98), Egypt/Beni-Seuf/01, Sul/01/09, D274, and IS/885/00 as well as vaccine strains derived from Massachusetts and 4/91, (8,18,19,24,25) have been detected.…”
mentioning
confidence: 99%
“…The disease is difficult to be controlled by IBV vaccines, which have been used widely in different chicken farms, because of the rapid circulation and complicated evolution of IBV strains. The chicken flocks have potential danger of IB outbreak when the serotype/genotype of vaccine strains are inconsistent to infective strains [20][21][22][23][24] . Therefore, it is important to choose a suitable IBV candidate vaccine strain to prevent the disease based on profound understanding of IBV epidemiology in China.…”
Section: Discussionmentioning
confidence: 99%
“…A vaccine programme with live-attenuated and inactivated vaccines of Massachusetts (Mass) serotype has been carried out widely and is partially successful in China. But in recent years, the phenomenon of IBV outbreaks occurred frequently in different vaccinated and non-vaccinated chicken flocks showed that the vaccines had poor or no protection against field virus [20][21][22][23][24] . Bing et al [25] found that the proportion of nephro-pathogenic type IBV is higher than any other types by analysis of the strains isolated from China in these years.…”
Section: Introductionmentioning
confidence: 99%